MiR-27a-3p and miR-30b-5p inhibited-vitamin D receptor involved in the progression of tuberculosis - Xiao, Min; Yang, Song; Zhou, An; Li, Tongxin; Liu, Jingjing; Chen, Yang; Luo, Ya; Qian, Chunfang; Yang, Fuping; Tang, Bo; Li, Chunhua; Su, Na; et al. (Frontiers in Microbiology, 2022)
Background MicroRNAs (miRNAs) play a vital part in tuberculosis (TB). Vitamin D receptor (VDR), a miRNA target gene, and its ligand, vitamin D3 (VitD3), have been reported to exert protective effects against TB. However, whether miRNAs can affect progression of TB by targeting VDR has not been reported. Methods Research subjects were selected according to the inclusion criteria. A clinical database of 360 samples was established, including the subjects’ general information, miRNA expression profiles and cellular experimental results. Candidate miR-27a-3p together with miR-30b-5p were screened and validated by high-throughput sequencing and qRT–PCR assays. Univariate and multivariate statistical analyses were performed. VDR and NF-kB p65 protein level were detected by Western blot assays. Proinflammatory cytokines expression levels were detected by ELISA. Luciferase assays and fluorescence-activated cell sorting (FACS) were further applied to elucidate detailed mechanisms. Results Differential miRNA expression profiles were obtained, and miR-27a-3p together with miR-30b-5p were highly expressed in patients with TB. These results showed that the two miRNAs were able to induce M1 macrophage differentiation and inhibit M2 macrophage differentiation. Moreover, experiments showed that the two miRNAs decreased the VDR protein level and increased the proinflammatory cytokines secretion by macrophages. Mechanistically, miRNAs targeted the 3’UTR of VDR mRNA and then downregulated VDR protein level by post-transcription regulation. Then, due to the reduction of VDR protein level, the NF-kB inflammatory cytokine signaling pathway was relieved, thus promoting progression of TB. Conclusions Our study not only identified differential expression miRNAs between the TB and control groups but also revealed that miR-27a-3p together with miR-30b-5p regulate proinflammatory cytokine secretion and macrophage differentiation through VDR in macrophages. Thus, the two miRNAs influence progression of TB.